The effects of armed conflict on forest cover changes across temporal and spatial scales in the Colombian Amazon - Bautista-Cespedes, Oscar V.; Willemen, Louise; Castro Nuñez, Augusto; Groen, Thomas A. (Springer, 2021)
This paper's results show that conflict variables have positive relationships with deforestation in Colombia; yet, they are not among the main variables explaining deforestation.